The Impact of Redistricting Proposals on Health Care Expenditures for Liver Transplant Candidates and Recipients. (18th January 2016) - Gentry, S. E.; Chow, E. K. H.; Dzebisashvili, N.; Schnitzler, M. A.; Lentine, K. L.; Wickliffe, C. E.; Shteyn, E.; Pyke, J.; Israni, A.; Kasiske, B.; Segev, D. L.; Axelrod, D. A.
Abstract: Redistricting, which means sharing organs in novel districts developed through mathematical optimization, has been proposed to reduce pervasive geographic disparities in access to liver transplantation. The economic impact of redistricting was evaluated with two distinct data sources, Medicare claims and the University HealthSystem Consortium (UHC). We estimated total Medicare payments under (i) the current allocation system (Share 35), (ii) full regional sharing, (iii) an eight‐district plan, and (iv) a four‐district plan for a simulated population of patients listed for liver transplant over 5 years, using the liver simulated allocation model. The model predicted 5‐year transplant volumes (Share 35, 29 267; regional sharing, 29 005; eight districts, 29 034; four districts, 28 265) and a reduction in overall mortality, including listed and posttransplant patients, of up to 676 lives. Compared with current allocation, the eight‐district plan was estimated to reduce payments for pretransplant care ($1638 million to $1506 million, p < 0.001), transplant episode ($5607 million to $5569 million, p < 0.03) and posttransplant care ($479 million to $488 million, p < 0.001). The eight‐district plan was estimated to increase per‐patient transportation costs for organs ($8988 to $11 874 per patient, p < 0.001) and UHC estimated hospital costs ($4699 per case). In summary, redistricting appears to be potentially cost saving for the health care system but will increase the cost of performing liver transplants for some transplant centers.